The evaluation of intra- and postoperative complications related to debulking surgery with bowel resection in patients with FIGO stage III–IV ovarian cancer. Issue 5 (1st September 2007) - Bidzinski, M.; Derlatka, P.; Kubik, P.; Ziolkowska-Seta, I.; Dańska-Bidzinska, A.; Gmyrek, L.; Sobiczewski, P.; Panek, G.
Abstract : The surgical treatment of advanced ovarian cancer is based on the maximal debulking with widening the operation range to the infiltrated organs. The aims are as follows: (1) the assessment of the quantity and quality of intra- and postoperative complications in patients with advanced ovarian cancer in which partial bowel resection was performed and (2) the evaluation of intra- and postoperative complications related to surgery with bowel resection and anastomosis, compared to Hartmann's procedure. The analysis of debulking procedures with intestinal resection and postoperative period in 39 ovarian cancer patients, FIGO stage III–IV, was performed. During 39 operations, the most frequent type of resection was the sigmoidectomy or proctosigmoidectomy (29 patients). In the remaining patients, left- and right-side hemicolectomy or partial enterectomy was done. Twenty-four anastomosis and 15 Hartmann's procedures were performed. There were no differences between surgery with anastomosis and Hartmann's procedure in aspect of quantity of complications, blood loss, and the time of surgery. There were no statistically significant differences in overall survival and progression-free survival in both groups. We conclude that the percentage of complications related to debulking surgery with intestinal resection in advanced ovarian cancer patients might be accepted. The quantity of complications related to surgery with anastomosis and to Hartmann's procedure is similar. If possible, the surgery with anastomosis should be performed.